Effect of surface treatment on the retention of zirconia crowns to tooth structure after aging - Monteiro, Renata Vasconcelos; dos Santos, Daniela Micheline [UNESP]; Bernardon, Jussara Karina; De Souza, Grace Mendonça (Wiley, 2020)
Objective: To evaluate the effect of different surface treatments on the retention between zirconia crowns and tooth structure after in vitro aging. Materials and methods: Human third molars (n = 44) received crown preparations and CAD/CAM zirconia crowns were manufactured. Specimens were divided into two groups: no aging, control (NAC, n = 11) or aging (A, n = 33). NAC were bonded with universal adhesive (UA). Aged specimens were divided into three subgroups (n = 11) according to surface treatment: Control: no abrasion + UA; Alumina: alumina abrasion + UA; Silica: tribochemical silica coating + UA. The crowns were cemented with dual-cure resin cement. Specimens in group A were aged by a combination of mechanical, thermal, and pH cycling. Retention strength values were obtained by tensile tests and results were analyzed by one-way analysis of variance (ANOVA) and Tukey test (P <.05). Results: Aging decreased the retention strength in control specimens (P <.001). Surface treatment improved the retention strength of aged specimens (P <.001), with similar results between alumina and tribochemical silica coating. Conclusion: The chemical interaction between the universal bonding system and zirconia's surface was not sufficient to withstand artificial aging. Tribochemical silica coating did not promote additional retention in comparison to alumina blasting. Clinical significance: The long-term retention of translucent zirconia crowns to tooth structure using phosphate-based materials is improved by means of mechanical surface treatments such as alumina blasting and tribochemical silica coating.
Keywords: aging; airborne particle abrasion; translucent zirconia; universal adhesive; zirconia crown